Beyond The Revival : Contemporary North West Native Art. (Vancouver : Charles H. Scott Gallery, 1989)
Adkins, Richard ; Afred, Wayne ; Bob, Dempsey ; Collinson, Alfred ; Davidson, Reggie ; Davidson, Robert ; Grant, Dorothy ; Hunt, Richard ; Hunt, Tony Jr. ; Hunt, Tony Sr. ; Jackson, Robert ; Janzé, Phil ; Livingston, John ; Mowatt, Ken ; Paul, Tim ; Point, Susan ; Robertson, Eric ; Stephens, Vernon ; Tallio, Glenn ; Thompson, Art ; Vickers, Roy ; Wilson, Lyle
Beyond The Revival : Contemporary North West Native Art, Charles H. Scott Gallery, Vancouver, Emily Carr College of Art & Design, July 25 to September 17, 1989
English
kunstcatalogus